Protecting optimal childhood growth: systematic nutritional screening, assessment, and intervention for children at risk of malnutrition in the Kingdom of Saudi Arabia - Murray, Robert D.; Shaaban, Sanaa Y.; Al Amrani, Mohammed; Aldekhail, Wajeeh; Alhaffaf, Faisal A.; Alharbi, Abdulaziz O.; Almehaidib, Ali; Al-Suyufi, Yasir; Al-Turaiki, Muath; Amin, Ahmed; Hasosah, Mohammed Y.; Alkhormi, Musa; et al. (Frontiers in Nutrition, 2024)
Background: In 2024, the Kingdom of Saudi Arabia Advisory Board on Pediatric Nutrition (KSA-ABPN) reviewed childhood undernutrition in the Middle East. We sought to foster efficient nutritional care for infants and children at nutritional risk. Severe malnutrition due to starvation is rare in Saudi Arabia, so we focused on early recognition and treatment of children with mild growth impairment that forewarns risk for further nutritional decline. This paper summarizes our findings and introduces a recommended guide for nutritional screening, assessment, and follow-up interventions.The KSA-ABPN aimed to build an algorithm with pathways and tools to facilitate up-todate nutrition-care practices for infants and children. The algorithm is intended to encourage consistent professional training-for and use-of validated tools, adoption of standardized thresholds for intervention, and delivery of nutritional support. Consistent care will increase opportunities for comparative analyses of various treatment strategies and their health and cost outcomes.We developed a 4-stage algorithm for identifying and caring for children at nutritional risk: (i) screening for clinical risk factors and age-related growth measures, (ii) observation of malnutrition-related physical signs, diet history, and/or laboratory detection of evidence indicating specific nutrient deficiencies, (iii) assessment of the severity of nutritional deficit, and (iv) development of a patient-specific Nutrition Care Plan that includes diet counseling, supplementation, routine monitoring, and follow-up.By helping professionals identify nutritional risk and specific nutritional deficits in infants and children early in the clinical course, we seek to expand quality nutritional care and ensure that children grow and develop fully.